Efektivitas Terapi Sholat terhadap Reduksi Kecemasan pada Anak Yatim Piatu: Studi Kasus di Panti Asuhan Baiti Jannati - Aimatul Hidayah, Assyifa (Theofani: Journal of Islamic Studies and Scholarly Discourse, 2025)
Anxiety disorder is a common psychological issue faced by orphans, particularly those residing in orphanages. The absence of parental figures, lack of emotional support, and social pressures often trigger chronic anxiety that affects children’s mental well-being. This study aims to analyze the effectiveness of prayer therapy in reducing anxiety levels among orphans at Baiti Jannati Orphanage in Purwokerto. Employing a qualitative case study approach, data were collected through in-depth interviews, participatory observation, and documentation involving two children undergoing regular prayer therapy. The findings indicate that performing prayer (sholat) with focus and devotion significantly contributes to inner calmness, reduction of anxiety symptoms, and enhancement of spiritual resilience. The ritualistic and contemplative aspects of prayer serve as essential tools in fostering psychological stability among the children. This study recommends integrating spiritual practices into social and mental health intervention programs for orphans.